Respostas
respondido por:
8
(x + 2) (x + 3) = 0
x^2 + 3x + 2x + 6 = 0
x^2 + 5x + 6 = 0
Delta = 5^2 - 4.1.6
Delta = 25 - 24
Delta = 1
x = - 5 + - raiz de 1 / 2
x = - 5 + - 1 / 2
x ' = - 5 + 1 / 2 = - 4 / 2 = - 2
x " = - 5 - 1 / 2 = - 6 / 2 = - 3
x^2 + 3x + 2x + 6 = 0
x^2 + 5x + 6 = 0
Delta = 5^2 - 4.1.6
Delta = 25 - 24
Delta = 1
x = - 5 + - raiz de 1 / 2
x = - 5 + - 1 / 2
x ' = - 5 + 1 / 2 = - 4 / 2 = - 2
x " = - 5 - 1 / 2 = - 6 / 2 = - 3
Perguntas similares
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás